Enabling Analysis of Big, Thick, Long, and Wide Data: Data Management for the Analysis of a Large Longitudinal and Cross-National Narrative Data Set. (August 2018) - Winskell, Kate; Singleton, Robyn; Sabben, Gaelle
Distinctive longitudinal narrative data, collected during a critical 18-year period in the history of the HIV epidemic, offer a unique opportunity to examine how young Africans are making sense of evolving developments in HIV prevention and treatment. More than 200, 000 young people from across sub-Saharan Africa took part in HIV-themed scriptwriting contests held at eight discrete time points between 1997 and 2014, creating more than 75, 000 narratives. This article describes the data reduction and management strategies developed for our cross-national and longitudinal study of these qualitative data. The study aims to inform HIV communication practice by identifying cultural meanings and contextual factors that inform sexual behaviors and social practices, and also to help increase understanding of processes of sociocultural change. We describe our sampling strategies and our triangulating methodologies, combining in-depth narrative analysis, thematic qualitative analysis, and quantitative analysis, which are designed to enable systematic comparison without sacrificing ethnographic richness.